ANALISIS KONSEPTUAL MANAJEMEN PENDIDIKAN ISLAM DALAM PERSPEKTIF AL-QUR'AN DAN HADIST: KAJIAN PUSTAKA - Rofiq, M. Ainur; Bahrani; Sudadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic education management based on the Qur'an and Hadith is a necessity in realizing holistic, authentic, and character-based governance of Islamic educational institutions. This study aims to identify the principles of Islamic education management contained in the Qur'an and Hadith, analyze their relevance to modern educational management functions, and formulate an integrative conceptual model of Islamic education management. The method employed is qualitative with a library research approach through content analysis technique and maudhui thematic method. The findings reveal that the Qur'an and Hadith contain fundamental managerial principles including amanah, 'adl, shura, tauhid, itqan, falah, and moral development, which are substantially relevant to the functions of planning, organizing, actuating, and controlling in modern educational management. This study also successfully formulates an integrative conceptual model that places tauhid as the central axis of all managerial activities with maqashid al-syari'ah as its evaluative framework. This model proves capable of comprehensively addressing the dichotomy between Islamic normative values and contemporary managerial approaches. This research contributes to strengthening the theoretical foundation of Islamic education management and provides normative guidance for Islamic educational institution managers in building governance that is effective, integrity-based, and spiritually dimensional.